2020
DOI: 10.1097/sla.0000000000003909
|View full text |Cite
|
Sign up to set email alerts
|

Association of Surgical Resident Wellness With Medical Errors and Patient Outcomes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 37 publications
(99 reference statements)
1
39
1
Order By: Relevance
“…Another important discovery in this analysis was regarding the well-being and burnout of residents of surgical programs during the pandemic. The depletion rate was higher than the traditional rates reported in the literature [ 16 , 22 , 23 ]. A national survey of general surgery residents in the United States reported a burnout rate of 33.1% [ 16 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Another important discovery in this analysis was regarding the well-being and burnout of residents of surgical programs during the pandemic. The depletion rate was higher than the traditional rates reported in the literature [ 16 , 22 , 23 ]. A national survey of general surgery residents in the United States reported a burnout rate of 33.1% [ 16 ].…”
Section: Discussioncontrasting
confidence: 61%
“…The burn out rate was higher than the traditional rates reported in literature. 8 , 9 , 10 Hewitt et al in a national survey of general surgery residents reported a burnout rate of 22%.9. In our study 65.1% of respondents reported having 5 or more days off per month during the pandemic, compared to 4 days per month before.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the PGY 1 class experienced more burnout than the other classes. 9 , 10 At this time, the immediate concerns pertaining to COVID-19 are on the forefront of research and planning. However, as time goes on, it can be anticipated that people will experience anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In OTS residents in France [ 27 ] and in US abdominal transplant surgery fellows, higher burnout was associated with a greater risk of having made a medical error in the past 3 months [ 48 ]. In a study of US general surgery residents, it was found that overall burnout and each of the emotional exhaustion and depersonalisation facets were significantly associated with a higher self-reported risk of having made a medical error that resulted in harm, and making a near-miss that did not result in harm [ 71 ].…”
Section: Consequences Of Burnoutmentioning
confidence: 99%